1981
DOI: 10.2307/2937307
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Ecology of Heliconia Herbivores: Experiments with Plant Fertilization and Alternative Hosts

Abstract: Efficiencies of food use, growth rates, and consumption rates were measured for larvae of eight tropical insect species, reared upon normal and fertilized Heliconia species (Zingiberales: Heliconiaceae) and Musa sp. (Zingiberales: Musaceae) in Costa Rica. Cephaloleia consanguinea and Chelobasis perplexa (Coleoptera: Chrysomelidae, Hispinae) feed only on Heliconia. Caligo memnon and Opsiphanes tamarindi (Lepidoptera: Brassolidae) are oligophagous, with known hosts in two families of Zingiberales. Sibine apicali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 72 publications
(125 reference statements)
1
35
0
1
Order By: Relevance
“…The Heliconia family is known to have chemical defenses against herbivores [27] and anecdotal brood mortality is known for Heliconia foraging honey bee colonies. The pollen of the flowers was collected in a 1.5 ml tube by shaking and scraping pollen from the anthers with a scalpel (45 mg pollen from 41 flowers).…”
Section: Methodsmentioning
confidence: 99%
“…The Heliconia family is known to have chemical defenses against herbivores [27] and anecdotal brood mortality is known for Heliconia foraging honey bee colonies. The pollen of the flowers was collected in a 1.5 ml tube by shaking and scraping pollen from the anthers with a scalpel (45 mg pollen from 41 flowers).…”
Section: Methodsmentioning
confidence: 99%
“…Elevated nitrogen levels in plant tissues may increase herbivore growth rates (Fox and Macauley 1977, Scriber 1979, Scriber and Slansky 1981, final adult weight Feeny 1977, Morrow andFox 1980), fecundity (Vince et al 1981, Prestidge 1982, and/ or overall survivorship (White 1969, McNeill and Southwood 1978, Morrow and Fox 1980. However, since phytophagous insects encompass many orders of arthropods that feed in markedly different ways, it is unrealistic to expect that such a diverse array of herbivores will respond similarly to changes in host quality (Stark 1965, Jones 1976, Auerbach and Strong 1981, Faeth et al 1981, Vince et al 1981, Brodbeck and Strong 1987.…”
Section: Introductionmentioning
confidence: 99%
“…Larcher (2000) suggested that the decrease of nitrogen content may be related to water stress. Plant tissues generally contain low concentrations of nitrogen with an average of 2.14 % (n = 400 plant species) (Auebach & Strong 1981). In Cerrado plants, this percentage is even lower (Marquis et al 2001).…”
Section: Resultsmentioning
confidence: 99%